Thioflavin dye degradation by using magnetic nanoparticles augmented PolyvinylideneFlouride (PVDF) microcapsules / Mohamed Syazwan Osman ... [et al.] - Mohamed Syazwan, Osman; Ka, Man Kong; Boon, Seng Ooi; Bassim H., Hameed; Jit, Kang Lim (2015)
Microcapsule has remarkable advantages in engineering application for pollutants removal and biomedical field for transportation. It has obviously drawn attention from the research community. Undeniably, it does have shortages but the key is to balance both the advantages and limitations to enhance microcapsule benefits. In environmental engineering applications, microcapsules could serve as encapsulation agents of nanoparticles (NPs) to drastically reduce the risk associated to nano-toxicity when it is indirect contact with surroundings. In addition, this technique could improve the physical contact and promote catalytic degradations of pollutants while exhibit better recyclability without loss of activity after multiple catalytic degradation cycles. Even though magnetic responsiveness of capsules can be used for ease of separation, one of the constraints is that the encapsulated particles will restrict the performance of capsules materials in pollutants removal. However, encapsulated magnetite particles interact with polymeric matrix chains and thus tying up the chains as knot which can restrict the expansions of whole capsules. Some-times, capsules shell is designated to remove certain target contaminants and so does for encapsulated particles. This may possibly reduce or increase the removal performance of integrated capsules which depends on the target contaminants and the underlying mechanism involved in pollutant removal. Hence, this work primarily focuses on the synthesis of magnetic nanoparticles augmented microcapsule with dual functionalities namely adsorptive and catalytic activities using membrane material, PolyvinylideneFlouride (PVDF). Feasibility study using Thioflavin dye as the representable model system for degradation will be explored.